Probing the Relationships Between Mandaeans (the Followers of John the Baptist), Early Christians, and Manichaeans - Brikha H. S. Nasoraia (Religions)
Mandaeism is the only ancient Gnostic religion surviving to the present day from antiquity. ‘Gnosticism’ was a block of creative religious activity mostly responding to the early Christian teachings in unusual ways of cosmicizing Jesus, and presenting a challenge to the ancient church fathers in the first-to-third centuries CE. Mandaeism, by comparison, has roots from John the Baptist rather than Jesus, although it is also important to recognize that this baptizing movement emerged in part as a survival of a very old indigenous ethno-religious grouping from Mesopotamia, its followers eventually settling in Mesopotamia’s middle and southern regions. Indeed, much of the Mandaeans’ thought and practice, especially their rituals of water ablution, have deep origins going back to Sumer, Akkad and Babylonia, reflecting regionally wide influences from right across the Fertile Crescent. Mandaean culture and the Mandaic Aramaic language was of high report in the so-called Patristic period covered by this Special Issue, even in the Arabian Peninsula up until the rise of Islam (634 CE onward), and Mandaeans were honored as a third “People of the Book”—the Sabians (Ṣābeʾun; or ṣobba in modern Iraqi Arabic)—in the Qur’an (2:62; 5:69; 22:17); in the Muslim world, many Mandaic speakers switched language to colloquial Iraqi Arabic and (Arabicized) Persian. This article aims to raise some basic questions, relevant to Patristics, about aspects of relationships between Mandaeans and both early ‘mainstream’ Christians and the other large grouping, the Manichaeans. These questions first concern the common flight of the followers of John and Jesus just before the Roman siege and destruction of Jerusalem (66–70 CE) and the role of the woman Miriai; second, the extent to which John and his followers affected the direction of early Christianity, and the consequences this had for ‘Baptist’/Christian relationships into the Patristic period, with attention paid to Mandaean views of Jesus; third, the process of the formation of early Mandaeism as it combined Hellenistic-Palestinian and Mesopotamian elements; and fourth, the signs that the Mandaeans not only influenced Mesopotamian Christian baptismal sects but were crucial in the emergence Manichaeism (from the 230s CE in Persian-dominated Iraq). This article will finish by concentrating on Mandaean–Manichaean relations in the light of a little known and previously secret Mandaic text (Diwan Razia), best known as Mani or Sidra d-Mani within a larger collection of unnamed occult texts. On the basis of the Mandaeans’ texts, we maintain that both Jesus and Mani apparently left their fold in turn.